2016
DOI: 10.1002/psp.2020
|View full text |Cite
|
Sign up to set email alerts
|

A Life-Course Analysis of Geographical Distance to Siblings, Parents, and Grandparents in Sweden

Abstract: This study makes a contribution to the demography and geography of kinship by studying how internal migration and demography shape the geographical availability of kin in contemporary Sweden. Age structures an individual's relationship with their parents and other kin, and this is reflected in how geographical distance to kin varies over the life course. This study uses a longitudinal approach in which the distance to siblings, parents, and grandparents is measured for the same individuals at different ages. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 54 publications
3
46
1
2
Order By: Relevance
“…Unlike Kolk (), who reported that gender differences are mainly related to the timing of leaving the parental home, we thus find persistent gender differences among adult Finns. This finding is in line with similar research on marital migration from Norway, although the Norwegian study concentrated on couples (Løken et al, ), and with the study by Chudnovskaya and Kolk () from Sweden, who found that adult daughter's lived further away from their mothers than adult men lived from their mothers at the time of the birth of the first child.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Unlike Kolk (), who reported that gender differences are mainly related to the timing of leaving the parental home, we thus find persistent gender differences among adult Finns. This finding is in line with similar research on marital migration from Norway, although the Norwegian study concentrated on couples (Løken et al, ), and with the study by Chudnovskaya and Kolk () from Sweden, who found that adult daughter's lived further away from their mothers than adult men lived from their mothers at the time of the birth of the first child.…”
Section: Discussioncontrasting
confidence: 95%
“…The persistent geographical attraction of close family members is similar to that reported in previous studies, for instance, Mulder and Kalmijn (), using Dutch data and Kolk (), using Swedish data. One novelty of our study is the inclusion of half siblings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in accordance with previous findings showing that adult children with divorced and separated parents remain in closer contact with their mothers than with their fathers (see, e.g., Daatland, ; de Graaf & Fokkema, ; Kalmijn, ). This finding also suggests the relevance of location‐specific capital in the decision to come back to the parental home, and more in general the relevance of the geographical distance between members of the kin network (Kolk, ). However, it is also worth noting that living in the same municipality had a relatively weak strengthening effect of family dissolution on coresidence, suggesting that many cross municipality borders to live with their parents in the face of divorce and separation.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Second, having multiple grandchild sets has been shown to produce weaker ties overall but to increase the likelihood of contact with at least one set (Fingerman 2004;Uhlenberg and Hammill 1998). The opportunities for individuals to engage with kin in Sweden are likely high, as most Swedes live relatively close to their kin networks (Kolk 2017), and individuals with many children are more likely to live close to at least one child (Holmlund, Rainer, and Siedler 2013). Given these two reasons, the sixth formulated hypothesis is that the more grandchild sets grandparents have, the earlier they retire.…”
Section: Theoretical Considerations Empirical Evidence and Hypothesesmentioning
confidence: 99%